2020
DOI: 10.1111/gcbb.12744
|View full text |Cite
|
Sign up to set email alerts
|

Associative nitrogen fixation linked with three perennial bioenergy grasses in field and greenhouse experiments

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Previous work on FLNF in association with other grasses suggests that FLNF may meet upward of 50% of plant N demands (Chalk, 2016; Kuan et al, 2016; Ladha et al, 2016). A similar estimate for switchgrass was confirmed in a recent study which showed potential for switchgrass to acquire one‐third of its N from FLNF (Wewalwela et al, 2020). In the context of previous studies, our work further highlights FLNF as an important N source to switchgrass cropping systems and underscores the potential for successful bioenergy production without fertilizer N addition.…”
Section: Discussionsupporting
confidence: 71%
“…Previous work on FLNF in association with other grasses suggests that FLNF may meet upward of 50% of plant N demands (Chalk, 2016; Kuan et al, 2016; Ladha et al, 2016). A similar estimate for switchgrass was confirmed in a recent study which showed potential for switchgrass to acquire one‐third of its N from FLNF (Wewalwela et al, 2020). In the context of previous studies, our work further highlights FLNF as an important N source to switchgrass cropping systems and underscores the potential for successful bioenergy production without fertilizer N addition.…”
Section: Discussionsupporting
confidence: 71%
“…The reasons miscanthus can maintain high yields without N fertilizer are poorly understood. For example, some studies using N budget estimates for miscanthus suggest a missing N source (Davis et al, 2010; Dohleman et al, 2012), implying endophytic or free‐living N‐fixing bacteria may be one source of this missing N (Davis et al, 2010; Eckert et al, 2001; Keymer & Kent, 2014; Wewalwela et al, 2020). Another plausible explanation is that miscanthus increases net N mineralization (N min ) (Davis et al, 2013, 2015), thereby meeting N demands with N mobilized from SOM.…”
Section: Introductionmentioning
confidence: 99%
“…Nebeská et al (2018) observed that the G + /G − and fungal/bacterial ratios in organic and toxic metals polluted soil increased after 2 years of Miscanthus cultivation through a greenhouse pot experiment. Several studies have reported the existence of diazotrophs in bulk and rhizospheric soil of land with cultivated Miscanthus (Zhao et al, 2020), and documented their considerable contribution to Miscanthus growth based on an analysis of a N fixation gene ( nifH ; Li et al, 2016; Soman et al, 2018; Wewalwela et al, 2020), but lacked revelations of the responses of soil N‐cycling‐related genes and the microbiome for long‐term Miscanthus conversion in Northern China.…”
Section: Introductionmentioning
confidence: 99%